Внутрішній аудит у протидії корупції та шахрайству в органах державного сектора України - Краєвський, Володимир Миколайович; Міщенко, Тетяна Михайлівна (Видавничий дім «Гельветика», 2025)
В статті визначено, що кардинального вирішення потребує питання протидії корупції в державних органах, оскільки фінанси бюджетної сфери є привабливим об’єктом уваги шахраїв та корупціонерів, а злочини в цій сфері посідають значну частку в структурі економічної злочинності. Аналіз тлумачень термінів «корупція» та «шахрайство» в міжнародних нормативних документах, вітчизняному законодавстві, в регламентах професійних та громадських організацій, в сучасних словниках економічної і правової термінології два можливість запропонувати тлумачення поняття «корупція та шахрайство у бюджетній сфері». Обґрунтовано необхідність залучення внутрішніх аудиторів для протидії корупційним проявам та шахрайським схемам, при цьому їх дії повинні фокусуватися: на оцінці заходів внутрішнього контролю; способах управління корупційними ризиками; документуванні та інформуванні керівництва і правоохоронних органів про виявленні підозри або факти. Вважаємо, що запропонований підхід до розуміння ролі внутрішнього аудиту у протидії корупції та шахрайству в органах державного сектора України сприятиме посиленню синергії спільних зусиль з державними антикорупційними органами та інститутів громадянського суспільства для остаточного подолання корумпованих взаємовідносин у сфері публічної влади.

The article determines that the issue of combating corruption in state bodies requires a radical solution, since the finances of the budgetary sphere are an attractive object of attention for fraudsters and corrupt officials, and crimes in this area occupy a significant share in the structure of economic crime. Analysis of the interpretations of the terms “corruption” and “fraud” in international regulatory documents, domestic legislation, in the regulations of professional and public organizations, in modern dictionaries of economic and legal terminology provides an opportunity to offer an understanding of the concept of “corruption and fraud in the budgetary sphere”. The results of the study revealed: the dynamics of the perception of corruption by citizens of the country and business; the level of prevalence of corruption in various areas of activity; methods of detecting fraud; units of a state body that have the highest risk of internal corruption and fraud; the dynamics of criminal proceedings related to corruption crimes for the period 2023–2024. It was established that the multifaceted nature of corrup- tion relationships gives rise to the existence of various types, forms, models and causes of corruption, understanding which is necessary for developing effective methods of preventing and overcoming corruption. The need to involve internal auditors to counteract corruption manifestations and fraudulent schemes is justified, since it is they who understand the “weak” points in the activities of a state body and are familiar with the peculiarities of the manifestation of corruption risks and fraud in the bud- get sector. It has been established that the focus of internal audit should be on assessing internal control measures and methods of managing corruption risks; documenting and informing management and law enforcement agencies about the detection of suspicions or facts. We believe that the proposed approach to understanding the role of internal audit in combating corruption and fraud in public sector bodies of Ukraine will contribute to strengthening the synergy of efforts of state anti-corruption bodies and civil society institutions to finally overcome corrupt relationships in the sphere of public power.
Keywords: корупція; шахрайство; внутрішній аудит; корупційні ризики; заходи реагування; corruption; fraud; internal audit; corruption risks; response measures